Dual task interference in children from 8 to 12 years old (Interferencia de las dobles tareas en niños de 8 a 12 años) - Adrià Marco-Ahulló; Raúl Fernández; Gonzalo Monfort-Torres; Pilar Bustillo-Casero; Jose Luis Bermejo; Xavier García-Massó (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. The main aim of this manuscript was to analyze the effect of dual task and their difficulty on the motor and cognitive performance using a postural control and a memory tasks in middle childhood group ages children, establishing the differences between the effect of the tasks in the different age groups. The study sample was composed by one hundred and sixteen children, between 8 and 12 years old. The participants completed three single tasks and two dual-tasks. The postural single task (EO) consisted in maintain the balance in the bipedal stance position and two cognitive single tasks performed were the Backward Digit Span Test with 3-Digits sequences length and the Backward Digit Span Test 5-Digits sequences length. The dual-tasks were the combination of the postural task and the cognitive tasks. Regarding the postural control measurement, CoP signals were acquired with a Wii Balance Board. The analysis performed showed that the younger groups (8-9 years old) had worse punctuations in postural control variables in dual-task conditions than the older age groups (11-12 years old), especially than the 12 years old group. Regarding the effect of dual task in postural control, in all groups between 9 to 12 years old, higher postural control and stability were observed during the execution of the 5D dual-task than during the 3D task. Finally, no differences were found in the number of correct answers in the cognitive task when performing a single or dual-task, in any age group.